(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The goal of this study was to address concerns about the extent to which students in class XII at Pelita Bangsa Christian High School Bandung internalized multicultural values through online learning of Indonesian history. The descriptive qualitative method is used in the research, then data collection techniques include interviews, observation, and documentation studies. According to the findings of this study, there are multicultural values embedded in online learning of Indonesian history. The multicultural values under consideration are tolerance, democracy, and equality. Students can interpret, give examples, and draw conclusions about the multicultural values that exist in learning Indonesian history. Teachers play an important role in the internalization of multicultural values when students learn Indonesian history online. For example, by connecting these multicultural values to contextual learning that is relevant to students’ lives. Pelita Bangsa Christian School Bandung as a multicultural school, has also been able to accommodate and teach students the application of multicultural values. Beginning with the most basic aspect called mutual respect.